The influence of the extraction temperature on polyphenolic profiles and bioactivity of chamomile (Matricaria chamomilla L.) subcritical water extracts. (15th January 2019) - Cvetanović, Aleksandra; Švarc-Gajić, Jaroslava; Zeković, Zoran; Jerković, Jelena; Zengin, Gokhan; Gašić, Uroš; Tešić, Živoslav; Mašković, Pavle; Soares, Cristina; Fatima Barroso, M.; Delerue-Matos, Cristina; Đurović, Saša
Highlights: Extraction of chamomile by subcritical water. Influence of temperature on chemical composition of obtained extracts. Biosensor DNA assays for antioxidant potential of extracts. Influence of temperature on biological activity of the extracts. Abstract: The main goal of this research was to determine the relationship among chemical structure, bioactivity and temperature of chamomile during subcritical water extraction in isobaric conditions (45 bar) at seven different temperatures (65–210 °C). The influence of temperature on phenolic profiles was defined by UHPLC-HESI-MS/MS. The overall results indicate that the presence of conjugated double bonds, side chains, glucose moiety or ether moiety in molecules influence the efficiency of polyphenols' extraction in subcritical water. In terms of antioxidant activity, the extracts were the most active towards ABTS radicals (IC50  = 7.3–16.8 µg/mL), whereby temperature of 150 °C was optimal. On the other hand, the extracts obtained at 115 °C showed highest cytotoxicity. Inhibition of α-amylase and α-glucosidase was the highest at 65 and 85 °C, i.e. 0.51 and 4.13 mmolAE/g, respectively. Activity against tyrosinase was the highest at 210 °C (17.92 mgKAE/g). The data showed that different non-phenolic compounds may also participate in bio-activities of the extracts.